2015
DOI: 10.1016/j.commatsci.2015.02.043
|View full text |Cite
|
Sign up to set email alerts
|

A mean field model of dynamic and post-dynamic recrystallization predicting kinetics, grain size and flow stress

Abstract: a b s t r a c tA physically-based two-site mean field model has been developed to describe the microstructural evolution due to recrystallization during and after deformation. The model has been applied to predict the recrystallized fraction, recrystallized grain size, and flow stress of 304L austenitic stainless steel during discontinuous dynamic recrystallization (DDRX), post-dynamic recrystallization (PDRX) and grain growth (GG). The model parameters vary with temperature and strain rate but do not depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…Cram [6] extended and successfully applied a physically based description for nucleation in static recrystallization to nucleation during dynamic recrystallization (DRX), and comparisons between experiment and model calculations showed good agreement over a wide range of deformation temperature, initial grain size, and applied strain rate. Beltran [7] developed and validated a model describing recrystallization in metallic materials capable of handling DRX, post-dynamic recrystallization (PDRX), and grain growth against experimental test cases for multi-pass hot deformation of 304L austenitic stainless steel, predicting microstructural evolution due to different recrystallization regimes through a modified Kocks-Mecking equation. Madej [8] compared the mean and full field dynamic recrystallization models and concluded that full field approaches additionally extend predictive capabilities of DRX models by incorporating microstructure evolution in an explicit manner.…”
Section: Introductionmentioning
confidence: 99%
“…Cram [6] extended and successfully applied a physically based description for nucleation in static recrystallization to nucleation during dynamic recrystallization (DRX), and comparisons between experiment and model calculations showed good agreement over a wide range of deformation temperature, initial grain size, and applied strain rate. Beltran [7] developed and validated a model describing recrystallization in metallic materials capable of handling DRX, post-dynamic recrystallization (PDRX), and grain growth against experimental test cases for multi-pass hot deformation of 304L austenitic stainless steel, predicting microstructural evolution due to different recrystallization regimes through a modified Kocks-Mecking equation. Madej [8] compared the mean and full field dynamic recrystallization models and concluded that full field approaches additionally extend predictive capabilities of DRX models by incorporating microstructure evolution in an explicit manner.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the predicted grain size distributions are improved as compared to former mean field models [14,15,16,17] even if their are still quite far from experimental ones.…”
Section: Introductionmentioning
confidence: 69%
“…This limitation is due to the fact that all grains which have nucleated at a given time have the same evolution (in size and dislocation density) in mean field models [14,15,16,17] whereas in a real microstructure, each grain evolves depending on 60 its own neighborhood. Therefore, in this work a new topological approach for the mean field modeling of DRX is proposed.…”
mentioning
confidence: 99%
See 2 more Smart Citations